Psychological Contract Fulfillment Improves Public Employee Performance - Sunarta, Sunarta; Wardana, Wardana; Nuranti, Barida Rakhma (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the role of psychological contract fulfillment in mediating the influence of achievement motivation and organizational commitment on employee performance. Data were obtained using a questionnaire distributed to respondents, then analyzed using Partial Least Square (PLS) based on Structural Equation Modeling (SEM). The results showed that achievement motivation had a direct effect on employee performance, psychological contract fulfillment was proven to mediate the effect of organizational commitment on employee performance, and organizational commitment had an effect on psychological contract fulfillment. The managerial implication of this study is that leaders need to provide employees with opportunities to excel, because achievement motivation contributes to producing better performance.